Deep-UVsensors based on SAW oscillators using low-temperature-grown AlN films on sapphires - Laksana, Chipta P.; Chen, Meei-ru; Liang, Yen; Tzou, An-jyeg; Kao, Hui-ling; Jeng, Erik S.; Chen, Jyh Shin; Chen, Hou-guang; Jian, Sheng-rui (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2011)
High-quality epitaxial AlN films were deposited on sapphire substrates at low growth temperature using a helicon sputtering system. SAW filters fabricated on the AlN films exhibited excellent characteristics, with center frequency of 354.2 MHz, which corresponds to a phase velocity of 5667 m/s. An oscillator fabricated using AlN-based SAW devices is presented and applied to deep-UV light detection. A frequency downshift of about 43 KHz was observed when the surface of SAW device was illuminated by a UV source with dominant wavelength of around 200 nm. The results indicate the feasibility of developing remote sensors for deep-UV measurement using AlN-based SAW oscillators.